Liniowe Tłumienie Nieliniowej Amortyzacji Pojedynczego Impulsu - Skowroński, J. (Engineering Transactions, 1958)
After discussing the design problems of the shock-absorbing system considered, and also physical assumptions and the scope of investigation, a model of the system is established with the corresponding equation of motion. The existing results of qualitative analysis of the case under conpasses to a description of consideration are summarized. Then, the author proximate methods of quantitative analysis for each particular range of damping parameters and elastic characteristic, confining his investigation to alternating motion with elastic characteristic of the rigid type. The calculations are accompanied by numerical examples. On the basis of approximate equations of phase trajectories, a discussion is entered into on the character of damping and the alternating motion of the shock-absorbing system, depending on various damping parameters and elastic characteristic. A numerical example of such a motion for various values of these parameters is included. Attention is drawn to the necessity of such an analysis for the designer of the shock-absorbing system in every case of design. This is necessary for selecting the optimum values of parameters.